Personality characteristics and conflict predispositions in teams Maritza and Rakovski from Bulgarian women's national volleyball league - Ivanov, I.; Kotev, V. (Journal of Applied Sports Sciences, 2019)
Introduction: In the game of volleyball, game efficiency is based not only on physical prepa-ration and technical skills. A great deal of it depends on the players` abilities to cooperate, com-municate and adapt to the psychosocial aspects of team group dynamics. In this study we attempt to establish the players` behavior in conflict situations, their basic personality characteristics and how these influence some game indicators.Methodology: 1) Background information; 2) Thomas-Kilmann Conflict Mode Instrument (1977); 3) Big Five Personality Test developed by Goldberg (1992).Results: The results of our research reveal that the scale with the highest result is Com-promising, which is the trait described by both assertiveness and cooperativeness. We have significant differences between teams and age groups in terms of the scale Competing from the Thomas-Kilmann Conflict Mode Instrument and Conscientiousness and Agreeableness from the Big Five PersonalityTest.Conclusions: The younger players are more open and try to find more information about the sports environment and learn more about the game and their personal growth. The higher the qualification and the age, the more the players prefer competing and being assertive in their interpersonal relationships. The lower level players prefer clearer rules and instructions. The players from Maritza are more sport aggressive and with a higher winners` attitude